Distinct Brain Dynamic Functional Connectivity Patterns in Schizophrenia Patients With and Without Auditory Verbal Hallucinations - Zhang, Yao; Wang, Jia; Lin, Xin; Yang, Min; Qi, Shun; Wang, Yuhan; Liang, Wei; Lu, Huijie; Zhang, Yan; Zhai, Wensheng; Hao, Wanting; Cao, Yang; et al. (Frontiers in Human Neuroscience, 2022)
Schizophrenia patients with Auditory verbal hallucinations (AVHs) are diseased groups of serious psychosis with still unknown etiology. The aim of this research was to identify the neurophysiological correlates of auditory verbal hallucinations. Revealing the neural correlates of auditory hallucination is not merely of great clinical significance, but it is also quite essential to study the pathophysiological correlates of schizophrenia. In this study, 25 Schizophrenia patients with AVHs (AVHs group, 23.2±5.35 years), 52 Schizophrenia patients without AVHs (non-AVHs group, 25.79±5.63 years) and 28 healthy subjects (NC group, 26.14±5.45 years) were enrolled. Dynamic functional connectivity was studied with a sliding-window method and functional connectivity states were then obtained with the K-means clustering algorithm in the three groups. We found that schizophrenia patients with AVHs were characterized by significant decreased static functional connectivity and enhanced variability of dynamic functional connectivity (non-parametric permutation test, Bonferroni correction, p<0.05). In addition, the AVHs group also demonstrated increased number of brain states, suggesting brain dynamics enhanced in these patients compared with the non-AVHs group. Our findings suggested that there were abnormalities in the connection of brain language regions in auditory verbal hallucinations. It appears that the interruption of connectivity from the language region might be critical to the pathological basis of AVHs.